Phytochemical composition and antioxidant properties of Canarium odontophyllum (Sarawak Olive): A seasonal fruit from Borneo, East Malaysia - Gilbert Ringgit; Bo Eng Cheong; Muhammad Dawood Shah; Shafiquzzaman Siddiquee (ResearchGate, 2025)
Background: Canarium species are reported rich of polyphenol, alkaloids, flavones, and saponins compounds. Canarium odontophyllum from Borneo’s variety, on the other hand is remaining unclear especially on the antioxidant activity towards radicals. Purpose: To investigate phytochemical composition and antioxidant properties of C. odontophyllum. Methods: Antioxidant properties were evaluated using 2,2-diphenyl-1-picrylhydrazyl-hydrate (DPPH) assay, 2,2′- azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) assay, and ferric-reducing antioxidant power (FRAP) assay with different polarity of extraction solvents (methanol, acetone and hexane). The phytochemical composition was determined by Liquid Chromatography Mass Spectrometry Quadrupole Time of Flight (LCMSQTOF). Results: Acetone showed the highest scavenging activity in the DPPH (0.0307 mg/ml) and FRAP (3.926 mg/ml) assays, while hexane exhibited the highest activity in the ABTS assay (0.119 mg/ml). The LCMS-QTOF chromatogram identified 22 potential compounds. Among these, the major compounds oleamide (10.49 %) and emmotin A (7.23 %) have previously been reported to exhibit antioxidant activity. Other health-beneficial compounds were also found, such as palmitic amide (2.46 %), deoxymiroestrol (6.23 %), and N-Cyclohexanecarbonylpentadecylamine (48.92 %), which are important in preventing metal corrosion, regulating hormones, and distinguishing between N-palmitoylethanolamine-hydrolyzing acid amidase (NPAA) and fatty acid amide hydrolase (FAAH), respectively. Conclusion: The results indicate that C. odontophyllum shows a promising potential an alternative drug in pharmaceutical developments.